PERKAWINAN SIRRI DALAM PERSPEKTIF HUKUM ISLAM DAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Armansyah, Armansyah (Fakultas Syariah IAI Muhammadiyah Bima, 2017)
Status of the unregistered marriages in social life is assumed as the unwritten marriages in Nation. Meanwhile, it is legal in Islamic perspective although it not written in Religion Office based on constitution. The problem effect of Unregistered Marriages based on constitution No 23, 2006 is the kid can not receive their personal identity right, document of born, document of marriages, card of family, card of nationality. In Islamic law, the marriages law is one of the aspect which more applied by most of Muslim in the word compared the muamalah. The marriages is the fundamental aspect or mitsaan galidan assumed legal if the requirements fulfilled based on al-Qur’an and Hadits. Scholars explained the requirements of marriages are candidate of husband, and wife, guardian of marriages, two witnesses, take and give (Ijab and qabul). The constitution No 1, 1947 chapter 2 verse (1) said that Marriages is legal if it done based on the Law of each religionand it trust.